Japan, its history, arts, and literature - Brinkley, Captain F. (J. B. Millet Co., 1901)
This book introduce about present Japan. Japan on the verge of history. Japan in the early eras of history. The Japanese in the nara epoch, the heian epoch, the heian epoch.